Comparison of placenta samples with contamination controls does not provide evidence for a distinct placenta microbiota. Issue 1 (December 2016) - Lauder, Abigail; Roche, Aoife; Sherrill-Mix, Scott; Bailey, Aubrey; Laughlin, Alice; Bittinger, Kyle; Leite, Rita; Elovitz, Michal; Parry, Samuel; Bushman, Frederic
Abstract Background Recent studies have suggested that bacteria associated with the placenta—a "placental microbiome"—may be important in reproductive health and disease. However, a challenge in working with specimens with low bacterial biomass, such as placental samples, is that some or all of the bacterial DNA may derive from contamination in dust or commercial reagents. To investigate this, we compared placental samples from healthy deliveries to a matched set of contamination controls, as well as to oral and vaginal samples from the same women. Results We quantified total 16S rRNA gene copies using quantitative PCR and found that placental samples and negative controls contained low and indistinguishable copy numbers. Oral and vaginal swab samples, in contrast, showed higher copy numbers. We carried out 16S rRNA gene sequencing and community analysis and found no separation between communities from placental samples and contamination controls, though oral and vaginal samples showed characteristic, distinctive composition. Two different DNA purification methods were compared with similar conclusions, though the composition of the contamination background differed. Authentically present microbiota should yield mostly similar results regardless of the purification method used—this was seen for oral samples, but no placental bacterial lineages were (1) shared between extraction methods, (2) present at >1 % of the total, and (3) present at greater abundance in placental samples than contamination controls. Conclusions We conclude that for this sample set, using the methods described, we could not distinguish between placental samples and contamination introduced during DNA purification.